Conceptual framework language - cfl - (2014)
This paper presents the Conceptual Frameworks Language -CFL-, it aims to bridge the gap between programming languages and design languages, using the mechanism of schematizing, this approach changes the complexity of the syntax of programming languages and complexity of the diagramming for ease of assembly and nesting of frames or conceptual blocks like Lego, we present the possibilities offered by CFL as a Language nearer to solving problems using computational and scientific vocabulary, which is transparent to the user, we outline comparisons and integrations with languages like java and UML, we propose metrics and develop the platform in java language.